„The Albanian Nation Embarked on Its March Through History With Sabre In Hand” : Analysis of the Historical Narrative of Socialist Albania - Vinš , Přemysl (Dějiny – teorie – kritika, 2013)
The historical narrative of Albania, constructed in the period between the end of the WWII and the early 1990s, was based on a Marxist-Leninist theory of a materialist conception of development of human society. It offered the Albanians an as yet most elaborate interpretation of their national history. Its creators aimed to present a scientific version of history but hand in hand with this effort, they also included various barely verifiable notions and events which had been, nonetheless, an important element of national identity. This is mainly the case of the origin of Albanians and their ancient, indigenous roots. The Albanian historical narrative played an important part in the legitimisation of the ruling elite, especially after the split from its former allies. With growing international and economic isolation of the country, Albanian history was becoming increasingly nationalist and a particular interpretation of the past could be used as a basis and justification of ideological attacks against the country’s enemies. It clearly displayed a strong tendency to search in the past for analogies with current developments. These analogies where then used to stabilise the status of the ruling elite and to mobilise the society.